2021
DOI: 10.1016/j.biopha.2021.111578
|View full text |Cite
|
Sign up to set email alerts
|

Will curcumin nanosystems be the next promising antiviral alternatives in COVID-19 treatment trials?

Abstract: The COVID-19 has become of striking interest since the number of deaths is constantly rising all over the globe, and the search for an efficient treatment is more urgent. In light of this worrisome scenario, this opinion review aimed to discuss the current knowledge about the potential role of curcumin and its nanostructured systems on the SARS-CoV-2 targets. From this perspective, this work demonstrated that curcumin urges as a potential antiviral key for the treatment of SARS-CoV-2 based on its relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 75 publications
0
48
0
2
Order By: Relevance
“…The thirty children are infected to post-COVID-19 Multisystem Infl ammatory Syndrome (MIS-C) in the control area. But it absolutely was interesting that under the 20 people showed as passive coronavirus carrier with absolute recovery in the 11-slum sample area, and it had been remarkable that no reinfection occurs within the middle and early cohort of all relations thanks to the consequences of biomedicine, TE or TMT, long-lasting potential immunity because of the presence of potential, effective and active phytochemical-constituents in curcumin of turmeric, etc., are signifi cantly active against COVID-19 [1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]28,29,33,35,37,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56]. So, this preventive treatment measures revealed that high-diluted-internal-potential-biomedicine, TE, or TMT, are highly effective in controlling diseases by boosting resistance against coronavirus with no side effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thirty children are infected to post-COVID-19 Multisystem Infl ammatory Syndrome (MIS-C) in the control area. But it absolutely was interesting that under the 20 people showed as passive coronavirus carrier with absolute recovery in the 11-slum sample area, and it had been remarkable that no reinfection occurs within the middle and early cohort of all relations thanks to the consequences of biomedicine, TE or TMT, long-lasting potential immunity because of the presence of potential, effective and active phytochemical-constituents in curcumin of turmeric, etc., are signifi cantly active against COVID-19 [1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]28,29,33,35,37,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56]. So, this preventive treatment measures revealed that high-diluted-internal-potential-biomedicine, TE, or TMT, are highly effective in controlling diseases by boosting resistance against coronavirus with no side effects.…”
Section: Resultsmentioning
confidence: 99%
“…It's reported that the potential therapeutic effect of turmeric contents against SARS-CoV-2 compared with experimental COVID-19 therapies, forming 'Wonder Drug as a safety measure for COVID19 Management' because of presence of various immune-boosting phytochemicals i.e. promising potential treatment methods or role of curcumin against this viral diseases or next promising nanosystems antiviral alternatives or the molecular mechanistic insights with relevance host-pathogen interaction and immunomodulation, and therefore the curcumin interact with S protein of SARS CoV2 and ACE2 of human plasma membrane insights from computational studies, and therefore the curcumin-piperine supplementation on clinical signs, duration, severity, and infl ammatory factors in patients with COVID-19 in a very structured summary of a study protocol for a randomised controlled trial, and it has proved the near 4000-year history of in-depth medical use in South Asia from the 'Golden Spice, Turmeric, Traditional Medicine to Modern Medicine' [10][11][12][13][14][15][16][17][18][19][20]. But it's created many problems regarding application costeffectiveness, and environmental friendliness, and biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamon ingredients similar to curcumin can be effective on various proteins contributing to the virus proliferation process [44] . A molecular docking analysis on key protein targets of SARS-CoV-2 predicts interaction of C. zeylanicum essential oil components (eugenol, linalool, (E)−cinnamaldehyde, (E)−cinnamyl acetate, β-caryophyllene, eugenyl acetate, benzyl benzoate) with the virus targets in the body.…”
Section: Potential Pharmacological Effects Of Cinnamon Against Covid-19mentioning
confidence: 99%
“…It inhibited the 3C-like protease (3CL pro ), and inhibition of ACE II receptor for its virus self-replication. The nanotechnology approach enhances the solubility of curcumin [19] . This is expected that nano-curcumin is more effective to target SARS-CoV-2 when PDT is applied.…”
Section: Dear Editormentioning
confidence: 99%